2005
DOI: 10.1111/j.1748-1716.2005.01501.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal endothelin system and excretory function in Wistar–Kyoto and Long–Evans rats

Abstract: The present data show that the selective ET(A) or ET(B) receptor blockade differentially affects tubular water and salt handling, which becomes apparent in conditions of low renal papillary endothelin receptor number and tissue endothelin-1 concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…With respect to the altered renal ET system in rats with spontaneous hypertension, which we found in the present and previous studies, it may be inferred that these are due to strain differences and are independent of BP alterations as we showed recently in Long-Evans rats [30] . In fact, the use of WKY rats as controls for SHR was challenged by some authors (for review, see Lindpaintner et al [31] ), but in the past and at present WKY rats were used as controls by most investigators, e.g.…”
Section: Discussionsupporting
confidence: 63%
“…With respect to the altered renal ET system in rats with spontaneous hypertension, which we found in the present and previous studies, it may be inferred that these are due to strain differences and are independent of BP alterations as we showed recently in Long-Evans rats [30] . In fact, the use of WKY rats as controls for SHR was challenged by some authors (for review, see Lindpaintner et al [31] ), but in the past and at present WKY rats were used as controls by most investigators, e.g.…”
Section: Discussionsupporting
confidence: 63%
“…In conscious animals (rats and dogs), antagonism of either ET A or ET B receptors has slight effects on basal RBF and GFR [837,843,[849][850][851] . ETA receptor blockade produces renal vasodilation and enhances pressure-dependent renin release [849,852] .…”
Section: Endothelin Effects On Renal Hemodynamicsmentioning
confidence: 99%
“…BQ-788 did not inhibit constriction (C and D). #Significant difference from sham for P Ͻ 0.05. synthesis that suggest plasma ET-1 levels are primarily regulated at the level of promoter activation (15,28) and that the kidney and heart are primary sites of ET-1 production (17,25). Several transcription factors have been identified that modulate ET-1 synthesis including hypoxia inducible factor (HIF) (11,41).…”
Section: ) Et B Receptor Mrna Expression Is Not Different In Tissuesmentioning
confidence: 99%